The Conference Cesare Battisti Geografo e cartografo di Frontiera, Trento 27-29th October, 2016 - Sergio Zilli (Almatourism, 2016)
Celebrations for the 100th anniversary of First World War necessarily had to include a tribute to life and works of Cesare Battisti, an irredentist native from the Trentino area as well as prominent geographer. The need for a tribute was first addressed by the conference entitled Cesare Battisti geografo e cartografo di frontiera, which was held in Trento on October 27-29, 2016, thanks to the initiative of the Dipartimento di Lettere e Filosofia (Department of Letters and Philosophy) of the Trento University and the Centro Italiano di Studi Geografici (Italian Center for Geographic Studies) in Rome.